Inroads of palm oil into the Middle East and North Africa region - Abdel Hameed, Amna Awad; Mohamed Arshad, Fatimah (Universiti Putra Malaysia Press, 2010)
The MENA region, with its expanding consumption and high dependence on imports, represents a good potential market of vegetable oils. Strong consumption growth for vegetable oils in general, and palm oil products in particular, coupled with limited vegetables oils production capabilities in the region, have been behind the increase in trade. further growth is anticipated in large part due to a strong regional GDP forecast. Palm oil is the most important imported oil in the region. Understanding the market demand for palm oil in this region entails a precise investigation of the determinants of the market fundamentals in that region, which provides valuable insights to the industry players as well as policy makers. This book is an attempt to examine the characteristics of the vegetable oils market with special focus on palm oil. It also evaluates the impact of policy instruments and market variables on the demand for palm oil in this area. Long term forecast are required mostly for formulating long-term targets and strategies. Hence, the book attempts to assess the oils and fats situation, discuss trade issues of fats and oils in the region and attempts to identify the potentiality of expanding palm oil market in the region through generating long run projections for the import demand for palm oil.